The Stories We Tell - Gaines, Joanna, 1978- ([New York] : Harper Select, 2022)
""I thought I'd found myself in a world that, in order for me to fit into it, I had to fold myself up and break myself down. But it's a tight squeeze in a box that's only good for hiding."--Joanna Gaines"--
Keywords: Gaines, Joanna, -- 1978-; Interior decorators -- Biography. -- United States; Television personalities -- Biography. -- United States; Women interior decorators -- Biography. -- United States; Women television personalities -- Biography. -- United States; Self-realization.; Self-perception.; Autobiographies; Self-help publications